The Ethical Dilemmas of a Rural Physician - Purtilo, Ruth (The Hastings Center report, 1986)
Physicians in rural settings confront many of the same ethical dilemmas as their urban counterparts: confidentiality, quality-of-life decisions, resource allocation, and their moral responsibility for bettering the life of the community. However, the courses of action they choose as morally justifiable are influenced by distance from other professional facilities, the interrelationship of private and professional roles in a small community, and the non-specialized orientation of their practices.